Optimal Allocation of Emergency Repair Resources for Producer–Consumer Communities Considering Fault Risk Classification and Emergency Repair Response Capability - Mao, Donghua; Qiu, Jinyi (Frontiers in Energy Research, 2022)
With the construction of new power systems, distributed power sources are connected in large numbers and the possibility of faults increases. The optimal allocation of repair resources is important to improve the fault management efficiency and the quality of power supply services in the producer-consumer community. Using a large number of historical fault resources accumulated in the producer-consumer community, we first preprocess the fault information by rough set theory, then establish an optimal allocation model that minimizes the total fault loss, considers fault risk classification and repair response capability, and finally uses the improved gray wolf optimization algorithm to perform the optimal calculation. To address the problems of the traditional gray wolf algorithm, Tent mapping is introduced in the generation of the initial population to enhance the uniformity of the initial population. The cooperative competition mechanism is introduced to improve the utilization of effective information among individuals. Finally, the feasibility and superiority of the algorithm are verified through the analysis of calculation cases. Finally, the feasibility of this configuration method is verified through the analysis of arithmetic cases.